2022
DOI: 10.2196/34832
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an Online Peer Gatekeeper Training Program for Postsecondary Students on Suicide Prevention in Japan: Protocol for a Randomized Controlled Trial

Abstract: Background Postsecondary student suicide is one of Japan’s most severe public health problems. Gatekeeper training (GKT) programs are a generally recommended suicide prevention intervention in Japan. For suicide countermeasures, an online program tailored to students may enhance self-efficacy as a gatekeeper. Objective This study aims to describe a research protocol to investigate the effect of a newly developed internet-delivered online peer GKT progra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…It should be noted that the three interventions that considered the COVID-19 situation and/or were developed after this event [41,53,55] within the Spanish sample were focused on prevention, which already denoted a growing interest in treating this problem, possibly aggravated by the crisis caused by the pandemic. In the Japanese sample, only one intervention included COVID and focused on treatment [25]. From the start of the COVID-19 pandemic in 2020, we did not find more published interventions for suicide compared to the rest of the years.…”
Section: Intervention Typesmentioning
confidence: 84%
See 3 more Smart Citations
“…It should be noted that the three interventions that considered the COVID-19 situation and/or were developed after this event [41,53,55] within the Spanish sample were focused on prevention, which already denoted a growing interest in treating this problem, possibly aggravated by the crisis caused by the pandemic. In the Japanese sample, only one intervention included COVID and focused on treatment [25]. From the start of the COVID-19 pandemic in 2020, we did not find more published interventions for suicide compared to the rest of the years.…”
Section: Intervention Typesmentioning
confidence: 84%
“…The analysis based on the criteria already presented showed that not all the interventions had a control group to compare their effects. A proportion of 4/23 in the Spanish sample [21][22][23][24] and 5/23 in the Japanese sample [25][26][27][28][29] included a control group exempt from treatment, although some had a group that received a different treatment, with a proportion of 5/23 in the Spanish sample [30][31][32][33][34] and 3/23 in the Japanese sample [35][36][37]. While, in the Japanese sample, two articles [38,39] included the relatives of the patient, in the Spanish sample we found two articles [24,40].…”
Section: Methodological Quality Analysismentioning
confidence: 95%
See 2 more Smart Citations